2015
DOI: 10.1007/s13577-015-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy mediates innate immune responses via fibroblast–macrophage interactions

Abstract: Antibacterial photodynamic therapy (PDT) has come to attract attention as an alternative therapy for drug-resistant bacteria. Recent reports revealed that antibacterial PDT induces innate immune response and stimulates abundant cytokine secretion as a part of inflammatory responses. However, the underlying mechanism how antibacterial PDT interacts with immune cells responsible for cytokine secretion has not been well outlined. In this study, we aimed to clarify the difference in gene expression and cytokine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Consistent with the mechanism of action of this therapy [124], the results revealed high TNF-␣ expression; however, the expression levels of IL-1 and IL-6 in the aPDT group were lower than and similar to those in the untreated group, respectively [123]. During the delayed phase reaction, neutrophil chemo-attractants and IL-1b are the factors regulating neutrophil migration [125]. With regard to peri-implantitis, this disease involves the destruction of alveolar bone, which leads to implant loss.…”
Section: Could the Inflammatory Response Activated By Apdt Modulate Bsupporting
confidence: 63%
“…Consistent with the mechanism of action of this therapy [124], the results revealed high TNF-␣ expression; however, the expression levels of IL-1 and IL-6 in the aPDT group were lower than and similar to those in the untreated group, respectively [123]. During the delayed phase reaction, neutrophil chemo-attractants and IL-1b are the factors regulating neutrophil migration [125]. With regard to peri-implantitis, this disease involves the destruction of alveolar bone, which leads to implant loss.…”
Section: Could the Inflammatory Response Activated By Apdt Modulate Bsupporting
confidence: 63%
“…However, fibroblasts and macrophages interact with each other to mediate the immune response. Activation of the NF-κB pathway then results to in enhanced secretion of pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β) and neutrophil chemoattractant MIP-2 and Cxcl1 from macrophages [36]. This evidence indicates that HSPA1B may be associated with the proliferation of CPIV3 in MDBK cells through an ability to interact with key components of the NF-κB pathway, moreover, those involved in innate immunity, but the detailed mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There are theoretical reasons to think that PDT and PT may be synergistic. PDT promotes the microenvironment to be more conducive to immunologic effect, can lead to an inflammatory reaction that can evoke a host anti‐tumor immune response, and can lead to immunogenic cell death . Recent reports have suggested that proton and heavy ion therapy may stimulate the immune system to a greater degree than photon therapy .…”
Section: Discussionmentioning
confidence: 99%